P PENGAMATAN KONVEKSI RAYLEIGH BENARD SEBAGAI REPRESENTASI PEMBELAJARAN FENOMENA ALAM MELALUI GERAK MOLEKUL AIR - M Hidayatur Rohman; Putut Marwoto; Retno Sri Iswari; Edy Cahyono (Jurnal Penelitian Pendidikan IPA, 2022)
Research has been carried out with a device to observe the phenomenon of Rayleigh Benard convection, made of a glass box bounded by a lower plate and an upper plate. The bottom plate is hotter than the top plate which functions to heat the horizontal fluid layer from below. This study aims to observe the phenomenon of water molecule movement. The observation medium was water mixed with teak sawdust as a representation of water particles with an average density of mean=0.99 g/cm3. The variation of water thickness (d) used 5 cm and 6 cm with variations in temperature difference (DT) with an average increase of 50°C. Data was collected with a cellphone camera and run with Windows Movie Maker software which has a time accuracy of up to 0.001 seconds. It was observed that an increase in the temperature difference (DT) between the two plates resulted in an increase in the velocity of motion of water particles in convection which is depicted by a v-DT diagram. Due to the difference in temperature (DT) also results in the movement patterns of water molecules, namely laminar and turbulent. The turbulent phase with the Rayleigh number value R~107, indicated that the flow of water particles is getting faster, the direction of the flow of the particles starts to become irregular and sometimes signs of a water vortex appear. At different fluid immersion results in the start of a turbulent phase. The turbulent phase for d=5cm is observed at DT~30°C, and d=6cm at DT~20°C. Furthermore, this RBC phenomenon is used as a representation of learning natural phenomena in air fluids, namely whirlwinds as an event due to differences in temperature and pressure of a fluid